The Epistle of forgiveness, or A pardon to enter the garden. - Abū al-ʻAlāʼ al-Maʻarrī, 973-1057 (Library of Arabic literature., 2014)
One of the most unusual books in classical Arabic literature, The Epistle of Forgiveness is the lengthy reply by the prolific Syrian poet and prose writer, Abu l-'Ala' al-Ma'arri (d. 449 H/1057 AD), to a letter by an obscure grammarian, Ibn al-Qarih. With biting irony, The Epistle of Forgiveness mocks Ibn al-Qarih's hypocrisy and sycophancy by imagining he has died and arrived with some difficulty in Heaven, where he meets famous poets and philologists from the past. He also glimpses Hell, and converses with the Devil and various heretics. Al-Ma'arri-a maverick, a vegan, and often branded a he.